Stress‐Induced 3D Chiral Fractal Metasurface for Enhanced and Stabilized Broadband Near‐Field Optical Chirality. Issue 15 (6th May 2019) - Tseng, Ming Lun; Lin, Zhan‐Hong; Kuo, Hsin Yu; Huang, Tzu‐Ting; Huang, Yi‐Teng; Chung, Tsung Lin; Chu, Cheng Hung; Huang, Jer‐Shing; Tsai, Din Ping
Abstract: Metasurfaces comprising 3D chiral structures have shown great potential in chiroptical applications such as chiral optical components and sensing. So far, the main challenges lie in the nanofabrication and the limited operational bandwidth. Homogeneous and localized broadband near‐field optical chirality enhancement has not been achieved. Here, an effective nanofabrication method to create a 3D chiral metasurface with far‐ and near‐field broadband chiroptical properties is demonstrated. A focused ion beam is used to cut and stretch nanowires into 3D Archimedean spirals from stacked films. The 3D Archimedean spiral is a self‐similar chiral fractal structure sensitive to the chirality of light. The spiral exhibits far‐ and near‐field broadband chiroptical responses from 2 to 8 µm. With circularly polarized light (CPL), the spiral shows superior far‐field transmission dissymmetry and handedness‐dependent near‐field localization. With linearly polarized excitation, homogeneous and highly enhanced broadband near‐field optical chirality is generated at a stably localized position inside the spiral. The effective yet straightforward fabrication strategy allows easy fabrication of 3D chiral structures with superior broadband far‐field chiroptical response as well as strongly enhanced and stably localized broadband near‐field optical chirality. The reported method and chiral metasurface may find applications in broadband chiral optics and chiral sensing. Abstract : An effective and single‐step nanofabrication method for a broadband 3D chiral metasurface is demonstrated in this work. The metasurface consists of 3D self‐similar Archimedean spirals and shows very broadband and significant chiroptical properties in the infrared regime. This work paves a novel route toward ultracompact chiral optical components and chiroptical sensing.